Report on the combat sports-related research at the 27th Annual Congress of the European College of Sport Science (Revista de Artes Marciales Asiáticas, 2023)
This short report describes the combat sports-related research presented at the 27th Annual Congress of the European College of Sport Science (ECSS), as well as the special session about this topic at the event. The Annual Congress of the ECSS is one of the most important events in the field of Sport Sciences worldwide, bringing together some of the leading researchers in this area. In 2022, it was held in Seville, Spain, from August 30 to September 2. Although combat sports and martial arts have their own specific events and journals, it is important that research conducted on these topics be presented to a broader audience. This presentation can increase awareness among other scientists regarding the relevance of these topics which, in turn, may have a positive impact on obtaining grant for research and positions in universities. Therefore, this report provides a brief overview of the martial arts and combat sports-related investigations presented at this event, along with some strategies to increase their visibility.Keywords: martial arts, conference, science, education.